2017
DOI: 10.3390/nano7010016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solution Properties and Process Parameters on the Formation and Morphology of YSZ and NiO Ceramic Nanofibers by Electrospinning

Abstract: The fabrication process of ceramic yttria-stabilized zirconia (YSZ) and nickel oxide nanofibers by electrospinning is reported. The preparation of hollow YSZ nanofibers and aligned nanofiber arrays is also demonstrated. The influence of the process parameters of the electrospinning process, the physicochemical properties of the spinning solutions, and the thermal treatment procedure on spinnability and final microstructure of the ceramic fibers was determined. The fiber diameter can be varied from hundreds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The CGO nanofibrous membranes proposed in this work are synthesized from a spinning water/ethanol-based solution containing the cations of interest (dissolved from nitrate salts), and an appropriate polymer (spinning polymer, PVP) that sustains the formation of nanofibers during the whipping step of the electrospinning process (evaporation of the solvent) [26,53,54]. A thermal treatment is conducted on the as-spun organic-inorganic nanofibrous substrate (green) to remove the organic component (spinning polymer) and to promote the formation of the crystallographic phase.…”
Section: Resultsmentioning
confidence: 99%
“…The CGO nanofibrous membranes proposed in this work are synthesized from a spinning water/ethanol-based solution containing the cations of interest (dissolved from nitrate salts), and an appropriate polymer (spinning polymer, PVP) that sustains the formation of nanofibers during the whipping step of the electrospinning process (evaporation of the solvent) [26,53,54]. A thermal treatment is conducted on the as-spun organic-inorganic nanofibrous substrate (green) to remove the organic component (spinning polymer) and to promote the formation of the crystallographic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be used in non‐aqueous solutions, as well. This polymer has showed extensive applications in the synthesis of nanostructures, since carbonyl group in pyrrolidone ring can make complex with many inorganic species …”
Section: Resultsmentioning
confidence: 99%
“…A further interesting antimicrobial strategy is the use of metallic nanoparticles, such as Ag NPs [73]; whereas synergic activity between silver ions release and hyperthermia caused by the photo-thermal effect under near-infrared laser irradiation occurs [74,75,76]. In this regard in a work by Ballesteros, the authors reported the use of nanogels that were loaded with metallic nanoparticles and presented the synergic activity of this platform after irradiation with a specific wavelength.…”
Section: Antibiotic Nanoparticlesmentioning
confidence: 99%